Institutional Violence Against Youth and Care and Memory Practices in the Chilean Social Revolt (Andamios, Revista de Investigación Social, 2025)
On October 18, 2019 in various cities of Chile began the “social revolt”, a series of social mobilizations demanding the recognition of social and economic rights after 17 years of civil-military dictatorship and thirty years of democratic transition. During these mobilizations, numerous human rights violations by the State were documented, affecting mainly young people. This qualitative study conducted in 2024 explores the experiences of eleven professionals who provided care to young people affected by police violence. The article characterizes state violence against youth, or juvenicide, as a counterinsurgency strategy and as a continuation of a repressive process initiated during the civil-military dictatorship. It also systematizes its consequences and describes practices of care and memory that emerged during and after the social revolt.
Keywords: Chile; youth; resistance; social revolt; state violence